Avaliação da capacidade combinatória de milho branco para canjica na região noroeste do Paraná - Bignotto, Lucas Souto (2011)
The market for the use of corn is diverse. Among the possibilities, the use of white corn to make grits has been effectively developed by small rural producers who need to aggregate value to their product. Although any sort of corn may be used in order to prepare grits, few materials present a good grain conversion into grits. In addition, just a few commercial materials for grits production are available for the Brazilian producers. The main objective of this work was to produce information to increase the development of new superior genotypes for this end. Thus, 28 hybrids resulting from a complete 8x8 diallel, with the parents and without the reciprocals, were evaluated in a randomized blocks design with three repetitions in the 2009/2010 and the 2010/2011 summer harvest. In those experiments, six characteristics were taken into account: grain yield, plant and ear height, grits yield, small grits yield, and grits residue. The data were submitted to analysis of variance to verify the existence of significant differences among treatments. The specific and general combining ability were estimated using the fixed model in method 2 by Griffing (1956). The heterosis effects were obtained by Gardner e Eberhart's methodology (1966). The information obtained allows to recommend the following hybrids IAC Nelore x HD 332, IPR 119 x HT 392 and IAC Nelore x HT 932 for grain profit, and the hybrids IPR 119 x HT 9332, HT 932 x HT 392 and IPR 119 x HD 332 for grits profit for the extraction of grain derivative, and the progenitors HT 9332 and HD 332 for hybrid combination or compound formation.